PENGEMBANGAN SISTEM PENGELOLAAN DATA KUALITAS AIR LIMBAH DOMESTIK PERKOTAAN - Wahjono, Heru Dwi (Center for Environmental Technology, 2009)
One of the activities undertaken within the framework of environmental sanitation management by the government is to publish a variety of regulations governing the wastewater disposal problem. Sources of pollution of the most dominant in urban areas are domestic wastewater. Government institutions through BPLHD have conducted regular monitoring of river water quality in Jakarta. Management of water quality data from domestic waste sources is needed to control river water pollution. This requires data management system of urban domestic waste water quality. In this article will be discussed the development of data management systems for domestic waste water quality with reference to the current applicable regulations.Ã‚Â Key words : water quality database, Ã‚Â domestic waste water quality